Identification of Creative Economy Potential in Cirebon City City Branding Efforts - Wafi, Abil Hibatul; Firmansyah, Mukhamad; Widjaja, Arni Muslimah Handayani; Kusumah, Dinar Oktaria Supardi (Indonesian Journal of Advanced Research, 2025)
Cirebon City has high local cultural wealth, ranging from batik, craft art, to traditional culinary, seen from this potential, the creative economy sector in Cirebon City is still relatively small contribution (BPS, 2022) . The method used in this research is a qualitative method with a purposive approach through interviews, observations, and analysis using content analysis. This research shows that creative economy actors in Cirebon City have a high enthusiasm for advancing local culture, through product innovation. However, intersectoral coordination remains weak. The government has facilitated programs such as training and product promotion, but understanding of the concepts of the creative economy and city branding remains unequal. Cross-sector collaboration and strengthened communication strategies are needed to optimize the potential of local culture in building a city's image.